2010 ASHRAE handbook refrigeration. (American Society of Heating, Refrigerating, and Air-Conditioning Engineers, 2010)
Annotation The 2010 ASHRAE Handbook-Refrigeration covers the refrigeration equipment and systems for applications other than human comfort. This book includes information on cooling, freezing, and storing food; industrial applications of refrigeration; and low-temperature refrigeration. Primarily a reference for the practicing engineer, this volume is also useful for anyone involved in cooling and storage of food products.
Keywords: Refrigeration and refrigerating machinery -- Handbooks, manuals, etc.; elektronické knihy; electronic books